ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN PENDEKATAN RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL)? Studi pada PT BPR SINAR KUTA Periode 2016-2018 - Gede, I Komang; Ratnawati, Tri (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2020)
The results of this study indicate that based on the analysis of the BPR Sinar Kuta NPL formula in 2018 increased every year 2016 = 2.55%, 2017 = 3.12%, and 2018 =3.75%. and Liquidity risk using two ratios, namely LDR and LAR, has increased anddecreased. This shows that BPR Sinar Kuta has good profitability towards third partyrefunds. GCG Bank Sinar Kuta also has very good management as evidenced from 2016 -2018 showing a good composite predicate by determining a healthy bank valuation matrixbased on Bank Indonesia Regulation No.13 and the predicate is that all the compositevalues are still in greater or equal rules with (?) 1.5. When viewed from CAR, BankSinar Kuta is ranked 5th, it shows that Bank Sinar as a BPR Bank has a reasonable levelof health. Keywords: Factor Analysis, Bank Soundness, Bank Performance, RGEC